A brief history of toxicology in France during the last two centuries (1789–1989). (2022) - Bonnemain, B.; Ricordel, I.
Abstract: The history of toxicology in France over the last two centuries has been marked by numerous authors who have progressively broadened the fields of investigation: initially concerned with criminal or accidental poisonings, they have also taken an interest in the environment, workers' health, doping and illicit products, the dangers of radioactivity or combat gases, the risks associated with drugs, etc. Often pharmacists, these toxicology experts were specialists in analytical chemistry and developed numerous methods to refine the detection and characterization of potentially toxic products, and to better understand the mechanisms of toxicity produced by these substances.